Clinically apparent adverse reactions to intra-wound vancomycin powder in early onset scoliosis are rare. (December 2017) - DeFrancesco, C. J.; Flynn, J. M.; Smith, J. T.; Luhmann, S. J.; Sawyer, J. R.; Glotzbecker, M.; Pahys, J.; Garg, S.; Vitale, M.; Farrington, D. M.; Sturm, P.; ,
Purpose: Spine surgeons have increasingly used intraoperative application of topical vancomycin powder (TVP) to prevent surgical site infections (SSIs). The goals of this study were to define the rate of pharmacological adverse reaction to TVP in young patients undergoing posterior spinal surgery and to summarise institutional variation in TVP dosing. Methods: This retrospective observational study included ten spine centres in the United States and one in Europe. Patients with early onset scoliosis who underwent posterior spine surgery were eligible for inclusion. Age, weight, TVP dose and surgery type were recorded. Surgeries where patient age was > 12 years were excluded. Pharmacological adverse reactions were defined as clinical instances of Red Man Syndrome, rash, nephrotoxicity, proteinuria, hepatotoxicity or ototoxicity. The rate of pharmacological adverse reaction to TVP was calculated. Dosing practices were summarised. Results: Patient age was in the range of seven months to 12 years (median ten years). Of 1398 observations, there was one possible pharmacological adverse reaction. This was in a ten-year-old, 20.4-kg female patient with neuromuscular sco-liosis undergoing growing rod implantation. She was dosed with 1500 mg of TVP and immediately developed a transient rash without systemic symptoms. This abated over minutes without any medical intervention. There were no other adverse reactions in the sample. The population rate of pharmacological adverse reaction was 0.072% (95% confidence interval 0 to 0.4). Significant variability in dosing practices existed between centres. Conclusion: Pharmacological adverse reactions to TVP are rare. Future work may establish evidence-based guidelines for TVP dosing based on patient weight and other variables.